Acute exposure to violent neighborhood crime and depressive symptoms among older individuals in Colombia. (September 2019) - Hessel, Philipp; Martínez Botero, María Alejandra; Cuartas, Jorge
Abstract: To assess the association between acute exposure to neighborhood violent crimes and depression we combined representative, individual-level and geo-coded data for individuals aged 60 years and above living in four major cities in Colombia from the 2010 Demographic and Health Survey (DHS) with objective information on the timing and location of violent crimes. Exploiting spatial and temporal variation in the occurrence of crimes we find that being acutely exposed to a violent crime is positively associated with the number of depressive symptoms. Highlights: Latin America suffers of high rates of violent crime and mental disorders. Research overlooked older individuals outside high-income countries. Acute exposure to crimes positively associated with depressive symptoms among older individuals. Acute consequences are moderate, but population burden potentially substantial.